Literature Review of Technology-Based Therapy for Schizophrenia Sufferers - Ni Ketut Citrawati; Dewa Gede Candra (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Schizophrenia is a type of mental disorder characterized by distortions in thinking, perception, emotion, language, sense of self, and behavior which can be cured if given effective psychosocial treatment and therapy by improving life skills and social skills training. This article aims to find out what technology-based therapies can be given to people with schizophrenia to help their healing process. Literature review was taken using three data bases namely Science Direct, EBSCOhost, and Proquest with the keywords Schizophrenia, Cognitive Therapy, Technology-Based Therapy, Computer Therapy. The PRISMA method was used for selection by establishing inclusion and exclusion criteria. In the end, based on the above criteria, 10 articles were determined to be analyzed. Technology-based therapy for people with schizophrenia is one of the main focuses that needs to be considered when undergoing treatment, both in hospitals, health centers, rehabilitation centers or at the patient's home to support the healing process of people with schizophrenia. There are several technologies that can be given to people with schizophrenia based on technology, either in the form of hardware or software. The most important thing is, the accuracy of choosing the therapy that will be given to the patient before it is given to the patient. With this technology, it can be used as a solution for providing therapy to schizophrenics during this pandemic.